Knowledge Status and Potential Impact of Socio-Economic Factors on the Spreading of COVID-19 in West African Countries - Deguenon, Esther; Dougnon, Victorien; Gnimatin, Jean-Pierre; Hounkpatin, Mathieu; Assogba, Phénix; Baba-Moussa, Lamine; Dougnon, Jacques (Al-Nahrain Journal of Science, 2020)
Background: The COVID-19 epidemic that has been going on since December 2019 and caused by the SARS-CoV-2 coronavirus has spread rapidly around the world and has been classified as a pandemic. The health systems of African countries, especially those of West Africa, are still primitive and there is growing concern about the care of infected people. The present study to assess the knowledge and socio-economic impacts related to the spread of COVID-19 in West Africa.Methods: This study was carried out in March 2020, through a descriptive observation and the collection of information by means of an online survey sheet throughout West African Countries. Total confidentiality was assured to the responders who participated at this study and data collected were coded and analyzed by using Microsoft Excel 2019.Results: A total of 1158 answers were collected. The results showed that, the most representative countries were Benin (38.5%), Ivory Coast (25.2%), Togo (12.8%), and Nigeria (10.9%). Concerning the status of people's knowledge of COVID-19, all respondents claim to be aware of this disease. The study carried out the importance of hands washing as a way to limit the virus spreading in west African population. Certain gestures which were ingrained in habits such as traveling with public transport have suffered a regression.Conclusion: Non-compliance with hygiene and sanitary measures may lead to the spread of the virus in West Africa and these countries may then be surprised by this pandemic.